2014
DOI: 10.1002/hyp.10260
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on the daily time step of snow telemetry data to model the snowmelt components of the hydrograph for small watersheds

Abstract: Daily time step data from National Resources Conservation Service snow telemetry (SNOTEL) stations were used to estimate components of the snowmelt-dominated hydrograph for three small watersheds in Colorado and Wyoming. Thirty-three years of SNOTEL data was paired with streamflow data to estimate the annual run-off volume (Q 100 ) and peak streamflow (Q peak ), as well as the timing of 20, 50, and 80% (t Q20 , t Q50 , and t Q80 ) of the annual streamflow. Multivariate regression models were derived from snow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Similarly, further investigations across medium scales, such as at the watershed scale (dendritic features in Figure 1a), could identify the scale of cold air drainage patterns. Such two future examinations could capitalize (Fassnacht et al ., 2014) on the regional density of SNOTEL stations in mountain region data by installing additional inexpensive, stand‐alone temperature sensors, such as those used here.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, further investigations across medium scales, such as at the watershed scale (dendritic features in Figure 1a), could identify the scale of cold air drainage patterns. Such two future examinations could capitalize (Fassnacht et al ., 2014) on the regional density of SNOTEL stations in mountain region data by installing additional inexpensive, stand‐alone temperature sensors, such as those used here.…”
Section: Discussionmentioning
confidence: 99%
“…While the monthly analysis is at a finer temporal resolution, a month is still an arbitrary human-defined time step. To determine snowpack climatology, Fassnacht and Derry [22] showed that using daily data was more appropriate [19][20][21]23].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how snow accumulation amounts [32,33] and snowmelt rates [34] influence streamflow timing is important for hydrologists for runoff forecasting [35,36]. Various metrics have been used to simplify the assessment of runoff timing.…”
Section: Introductionmentioning
confidence: 99%